Study of HSG findings in our clientele: a multicentre retrospective analytical study - Yazdani, Shahla; Patil, Deepak; Mitra, Sujoy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Infertility is a social morbidity for an infertile couple. The treatment is exhaustive and expensive. Methods: Hysterosalpingography is a basic investigation for an infertile lady. We assessed the findings and outcome of HSG over one year at our tertiary care centers. Results: Bilateral patent fallopian tubes and normal uterine cavity were the commonest finding. Pain was the commonest complication in the procedure. Going for diagnostic hystero-laparoscopic was the commonest surgical intervention following HSG. Starting ATT was the commonest medicine intervention. ART Treatment involved starting intrauterine insemination cycle following HSG. Spontaneous conception was a welcome outcome in a selected subset of patients. Conclusions: HSG is an inexpensive and OPD based investigative modality. It is effective test for evaluation of infertility especially in low-resource settings. It is a stepping stone to guide further treatment in an infertile couple. A well timed and well exposed film can give numerous insights about the options for cure of this morbidity.